2014
DOI: 10.1155/2014/263625
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Mediated Bone Destruction in Rheumatoid Arthritis

Abstract: Bone homeostasis, which involves formation and resorption, is an important process for maintaining adequate bone mass in humans. Rheumatoid arthritis (RA) is an autoimmune disease characterized by inflammation and bone loss, leading to joint destruction and deformity, and is a representative disease of disrupted bone homeostasis. The bone loss and joint destruction are mediated by immunological insults by proinflammatory cytokines and various immune cells. The connection between bone and immunity has been inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
103
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 161 publications
2
103
0
1
Order By: Relevance
“…Curcumin is also involved in osteoclastogenesis via signalosome-associated kinases and the proteasome-ubiquitin system. Studies by Yang et al [7] and Jung et al [10] found that curcumin inhibited inflammatory activity via activation of enhancing nuclear factor erythroid-derived 2-like 2 in patients with type 2 diabetes and murine macrophages, respectively. Furthermore, curcumin is known as "the king of spices" on account of its epigenetic regulatory properties with regard to preventing cancer and neurologic and inflammatory diseases, such as breast carcinoma, osteogenic sarcoma, osteoarthritis, and neurocognitive disorders [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Curcumin is also involved in osteoclastogenesis via signalosome-associated kinases and the proteasome-ubiquitin system. Studies by Yang et al [7] and Jung et al [10] found that curcumin inhibited inflammatory activity via activation of enhancing nuclear factor erythroid-derived 2-like 2 in patients with type 2 diabetes and murine macrophages, respectively. Furthermore, curcumin is known as "the king of spices" on account of its epigenetic regulatory properties with regard to preventing cancer and neurologic and inflammatory diseases, such as breast carcinoma, osteogenic sarcoma, osteoarthritis, and neurocognitive disorders [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…The maintenance of bone mass relies on a balance between osteogenesis by osteoblasts and bone resorption by osteoclasts [6]. Stimulation of the muscles, synovium, and articular cartilage in a joint by wear debris results in a persistent disequilibrium of bone homeostasis that leads to abnormal of osteoclasts [7]. Wear debris consists of metal, polyethylene (PE), or ceramic particles depending on the contact interface material used between the joint components.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that cytokines and immune cells may have a direct osteoclastogenic effect (Jung et al. 2014) and also activate the HPA axis, with the resultant release of glucocorticoids. MDD may result in behavior changes, such as increased alcohol and nicotine intake, unhealthy nutrition, and decreased physical activity (Brot et al.…”
Section: Introductionmentioning
confidence: 99%
“…RA, a chronic autoimmune disease characterized by bone destruction, erosion, and inflammation in synovial joints, can result in osteopenia and osteoporosis in severe cases [6][7][8]. Several studies suggest that irregular osteoclast activation is involved in bone destruction of RA.…”
Section: Introductionmentioning
confidence: 99%